No lines: Observations from a pilot project to re-imagine, design and implement a flexible student-centred approach to study mode selection - Bevacqua, John; Colasante, Meg (Journal of University Teaching and Learning Practice, 2019)
Upon enrolling in a university course, students typically commit to a predetermined study mode: on-campus, online, or a hybrid/blended study mode. The education provider typically predetermines which study mode/s are available for each course. In this paper, the authors address the challenges of designing and trialling a new “StudyFlex” student-centred study mode at La Trobe University. By re-imagining the concept of flexibility in study mode selection, StudyFlex does away with bright line distinctions between online, blended and on-campus offerings and empowers students to self-select and adjust their preferred study mode pathway within their subject and throughout their course. This paper exposes and acts as a primer for discussing the many challenges of designing, developing, and implementing such student-centred study mode innovations. Specifically, it outlines and expands upon the StudyFlex trial conducted across several subjects, its genesis and justification, with its central tenet of designing subjects which allow students freedom to move between on-campus and online modes of learning within a single offering. Discussion extends to similar trial findings, including the recent pilot by Southern Cross University of a “converged delivery” model which attempted to merge on-campus and online study modes into a single converged mode. Attention then turns to curriculum development and design challenges inherent in the StudyFlex proof of concept. Particular emphasis is placed upon the imperative and significant challenge of ensuring equivalence of learning experience, in terms of learning value and quality, irrespective of the bespoke study mode pathway chosen by students in the StudyFlex trial subjects. The discussion culminates in identifying and highlighting the need for further research to address the challenges posed by innovations like the StudyFlex pilot and its predecessors such as the Southern Cross University converged delivery pilot. These extend to administrative challenges posed for universities seeking to accommodate student-centred study mode flexibility and potential and current practical regulatory constraints affecting such innovations. Fundamental questions emerge concerning the gap between the vision of allowing students to complete self-determination insofar as selection of study mode and the pragmatic realities of the various constraints facing higher education providers in seeking to push the boundaries of curriculum development and design to realise that vision. At a local level, and as the model becomes more widely adopted, La Trobe University teachers will need to be well supported to ensure their practices adapt to a new teaching model, while the model itself will need ongoing concerted design attention to ensure that students experience quality learning regardless of their study mode choices.